Obstacles and opportunities: Recent Kurdish struggles for political representation and participation in Turkey - (:unkn) unknown (My University, 2011)
Having gone through different phases of political action and facing various forms of suppression by the state, the Kurdish movement from 1990's persisted in establishing legal parties despite recurrent bans by the Constitutional Court. In the 2007 national elections DTP (after its ban the BDP) running as independent candidates formed a group in the Parliament which was followed by an extensive regional representation in eastern and southeastern Turkey in local elections of 2009. At the three levels of political activity (parliament, local government, civil society) the extent of women's presence exceeds well over the general percentage in Turkey while various civil society organizations at both the national and regional levels lend support for extension of minority/human rights. Although the new legal and political reforms as of early 2000's in line with Turkey's bid for accession to the EU have opened up a new venue for legitimization of Kurdish identity and recognition of various cultural, civil and cultural rights, strictness of the electoral law impedes fair representation and certain discriminatory attitudes and practices still persist in the civil and military bureaucracy, mass media and political parties in contention. Whether Kurdish participation in Turkey's politics will fare in 'normal' terms in the future is largely dependent on Turkey's democratization process in which the Kurdish politicians' claims to function as a non-regional Turkey party constitute an important but only one of the impacting factors, e.g., rehabilitation of the PKK, decentralization and empowerment of local government, extension of human rights, and a non-exclusionary definition of Turkish identity. © 2011 Brill.
Keywords: CIVIL SOCIETY INITIATIVES; CONSTITUTION; DEMOCRATIZATION; ELECTORAL LAWS; KURDISH PARTIES; LOCAL GOVERNMENT; MINORITY/HUMAN RIGHTS DEFICITS; PARLIAMENTARY REPRESENTATION